Visit Ujung Kulon National Park - Abdul Haris Mustari (Media Konservasi, 1997)
Ujung Kulon National Park is situated in the western point of the mainland of Java. A seven days trip to the national park was carried out in December 1996. Seven species of mammals, 35 species of birds, 2 species of reptiles and 102 species of plants were recorded during the fieldtrip. The mammals species could be observed during the fieldtrip were Black giant squirrel (Ratufa bicolor), Colugo (Cynocephalus variegatus), Largeflying fox (Pleropus vampyrus), Long-tailed macaque, Javan rusa (Cervus timorensis), Barking deer (Muntiacus munfjak) and Banteng (Bos javanicus). Of the bird species, White-bellied sea-eagle (Haliaeetus leucogaster), White-collared kingfisher (Halcyon chloris), Southern pied hombill (Anthracoceros convexus), White-rumped shama (Cop~ychus malabaricus) were among the most frequently observed birds species.Monitor lizard (Varanus satvator) and sea-snake could be observed in this area. A group of banteng consists of 23 individuals was observed grazing in Cigenter feeding ground. This feeding ground plays an important role for the herbivores. The invasion of the pioneer species threatens the existence of the feeding ground.Keywords : vegetation, wildlife, biodiversity, conservation